2013
DOI: 10.1186/2046-9063-9-18
|View full text |Cite
|
Sign up to set email alerts
|

The structure of winter phytoplankton in Lake Nero, Russia, a hypertrophic lake dominated by Planktothrix-like Cyanobacteria

Abstract: BackgroundThe permanent dominance of Planktothrix-like сyanobacteria has been often reported for shallow eutrophic\hypertrophic lakes in central Europe in summer\autumn. However studies on phytoplankton growth under ice cover in nutrient-rich lakes are very scarce. Lake Nero provides a good example of the contrasting seasonal extremes in environmental conditions. Moreover, the ecosystem underwent a catastrophic transition from eutrophic to hypertrophic 2003–05, with dominance of filamentous cyanobacteria in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…In winter 1971 and 2010, small flagellates from the genus Cryptomonas had high contribution in the phytoplankton biomass under the ice cover, and they were present in the whole studied water column. These species can grow under a thick ice cover and despite extremely low values of light and temperature, they are able to cause under-ice blooms (Phillips, Fawley 2002a,b;Babanazarova et al 2013). Periodically (January and March 2006), other flagellate species -Mallomonas akrokomos (Chrysophyceae) − occurred in large numbers beneath the ice of Lake Piaseczno.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In winter 1971 and 2010, small flagellates from the genus Cryptomonas had high contribution in the phytoplankton biomass under the ice cover, and they were present in the whole studied water column. These species can grow under a thick ice cover and despite extremely low values of light and temperature, they are able to cause under-ice blooms (Phillips, Fawley 2002a,b;Babanazarova et al 2013). Periodically (January and March 2006), other flagellate species -Mallomonas akrokomos (Chrysophyceae) − occurred in large numbers beneath the ice of Lake Piaseczno.…”
Section: Discussionmentioning
confidence: 99%
“…Also Peridinium bipes (Dinophyceae) was an important component of the phytoplankton community in 2003 and 2010 with the highest biomass in the water layer immediately beneath the ice cover. Development of the species from the genus Peridinium and their temporary high contribution in the winter phytoplankton biomass in lakes of different trophic status is very common (Danilov, Ekelund 2001;Philips, Fawley 2002a;Babanazarova et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High species diversity has been found under ice despite unfavorable conditions, including limited light availability, low water temperatures, restricted air-water gas exchange and prevention of wind-induced mixing (Salonen et al, 2009, Schröder, 2013. The concentration of nutrients and dissolved organic carbon may help to drive the plankton dynamics (Babanazarova et al, 2013). Griffiths et al (2017) examined the shifts in diatom assemblages from ten High Arctic lakes, lakes and concluded that ice cover is likely the principle driver of some of the most important ecological changes, resulting in increased diversity and the emergence of novel growth forms and epiphytic species.…”
Section: A R T I C L E I N F Omentioning
confidence: 99%